Feasibility of a Virtual Reality System in Speech Therapy: From Assessment to Tele-Rehabilitation in Children with Cerebral Palsy - Gloria Mangani; Veronica Barzacchi; Clara Bombonato; Jessica Barsotti; Elena Beani; Valentina Menici; Carolina Ragoni; Giuseppina Sgandurra; Benedetta Del Lucchese (MDPI AG, 2024)
Background/Objectives: New advances in technologies are opening the possibility to support functional evaluation and rehabilitation in the field of speech therapy. Among available systems, a virtual reality rehabilitation system (VRRS, Khymeia) is a multi-domain ecosystem. Despite it being used in a limited number of studies, its use in speech-therapy has shown potential for promoting linguistic and literacy skills. Methods: This pilot study aims to assess the feasibility of single-session speech assessment with the VRRS in twenty-eight children with cerebral palsy (CP) by means of ad hoc questionnaires. Moreover, we evaluated the feasibility and the effects of an intensive tele-rehabilitation treatment with the VRRS in a subgroup of three children with unilateral CP. Results: Feasibility was generally good when using the VRRS for assessments. Both clinicians and children found it to have good usability, although acceptability scores were higher for children than clinicians. For tele-rehabilitation, overall improvements were observed in both linguistic and learning (reading and writing) skills. Conclusions: This study paves the way for VRRS use in speech-therapy tele-rehabilitation for children with CP and language and learning difficulties.